PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ETNOMATEMATIKA MENGGUNAKAN MODEL RME UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD - Landong, Ahmad; Kintan Muthia Suci; Asya Afrida; Dini Aulia; Indah Sekar Wangi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a mathematics learning media based on ethnomathematics using the Realistic Mathematics Education (RME) approach, integrating the local culture of the Bagas Godang traditional house. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were fifth-grade students at SD IT Riadhul Habibi. The results indicate that the developed media is valid based on evaluations by media experts, material experts, and test item experts, and received positive responses from both teachers and students. Furthermore, the media effectivelyenhanced students' critical thinking skills, as evidenced by significant improvements in pretest and posttest scores, with high N-Gain values. Incorporating local cultural elements into the learning media made mathematics learning more contextual, meaningful, and engaging. However, some limitations remain, such as the lack of written educational information and the absence of usage guidelines. Therefore, further development is recommended to refine the media and expand its application across more diverse educational settings.